Properties Of Ground Coal Bottom Ash And Blast Furnace Slag Ternary Blended Cement, Mortar And Concrete - Liew, Jia Jia (2022)
The coal bottom ash (CBA) can be classified as Class F pozzolanic material according to ASTM C618 and used as a constituent binder in concrete. In the prior research, the CBA was pulverized in a laboratory ball mill to be used as supplementary cementitious material (SCM). However, the optimum milling parameters was not investigated to achieve the optimum output rate and quality of ground coal bottom ash (GCBA). Therefore, CBA was subjected to pulverization at various retention time, angular velocity of mill and CBA to instantaneous media ratio to determine the optimum milling parameters of the GCBA. Subsequently, the physical and chemical properties of the blended cement containing up to 50% of GCBA and ground granulated blast furnace slag (GGBS) was evaluated to determine the optimum combination ratio of the GCBA and GGBS.